Functionalized Selenium Nanotherapeutics Synergizes With Zoledronic Acid to Suppress Prostate Cancer Cell Growth Through Induction of Mitochondria-Mediated Apoptosis and Cell Cycle S Phase Arrest - An, Yulin; Zhao, Jianfu (Frontiers in Oncology, 2021)
The use of established drugs in new therapeutic applications has great potential for the treatment of cancers. Nanomedicine has the advantages of efficient cellular uptake and specific cell targeting. In this study, we investigate using lentinan-functionalized selenium nanoparticles (LET-SeNPs) for the treatment of prostate cancer (PCa). We used assays to demonstrate that a combination of LET-SeNPs and zoledronic acid (ZOL) can reduce PCa cell viability in vitro. Stability and hemocompatibility assays were used to determine the safety of the combination of LET-SeNPs and ZOL. The localization of LET-SeNPs was confirmed using fluorescence microscopy. JC-1 was used to measure the mitochondrial membrane potential, while the cellular uptake, cell cycle and apoptosis were evaluated by flow cytometry. Finally, cell migration and invasion assays were used to evaluate the effects of the combination treatment on cell migration and invasion. Under optimized conditions, we found that LET-SeNPs has good stability. The combination of LET-SeNPs and ZOL can effectively inhibit metastatic PCa cells in a concentration-dependent manner, as evidenced by cytotoxicity testing, flow cytometric analysis, and mitochondria functional test. The enhanced anti-cancer effect of LET-SeNPs and ZOL may be related to the regulation of BCL2 family proteins that could result in the release of cytochrome C from the inner membranes of mitochondria into the cytosol, accompanied by induction of cell cycle arrest at the S phase, leading to irreversible DNA damage and killing of PCa cells. Collectively, the results of this study suggest that the combination of SeNPs and ZOL can successfully inhibit the growth of PCa cells.